Peripheral vestibular disorders: an epidemiologic survey in 70 million individuals - Hülse, Roland; Hülse, Manfred; Schell, Angela (Otology & neurotology, 2019)
Background:Dizziness is a common complaint in medicine. Nevertheless, there is a lack of valid data concerning the age and gender distribution of dizziness disorders within a larger population. Therefore, the aim of the present study is to undertake a representative epidemiological survey that exami